Fostering Scientific Literacy in Young Children Through Small-Scale Fish Farming - Solikhatin Solikhatin; Ahmad Yusuf Sobri; Pramono Pramono (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study aims to foster scientific literacy in young children through small-scale fish farming activities integrated into school-based learning, emphasizing experiential, hands-on learning processes that are contextual and meaningful for children. Using approach qualitative with design studies case, research This dig phenomenon in a way deep in specific context. Data is collected through observation direct, semi- structured interviews with teachers, parents, and children, as well as discussion group focused (FGD). Research results show that activity cultivation fish scale small become an effective learning medium in integrate literacy science to in activity daily children. Activities This No only help children understand draft like ecosystem, cycle life fish, and its importance guard environment, but also develop skills social like cooperation and communication. Teachers and parents report existence improvement enthusiasm child to science as well as better understanding? deep after follow activity This. Research This own implications important , namely that learning based on experience like cultivation fish scale small can become a relevant and attractive alternative model For applied in education child age early. Besides that, the findings This support development curriculum based on an integrating environment theory with practice in a way balanced. With Thus, research This expected can push policy more education? inclusive, contextual, and learning-oriented based on experience